Temporal and spatial control of gene expression in horticultural crops - Dutt, Manjul (Hortic Res, 2014)
Biotechnology provides plant breeders an additional tool to improve various traits desired by growers and consumers of horticultural crops. It also provides genetic solutions to major problems affecting horticultural crops and can be a means for rapid improvement of a cultivar. With the availability of a number of horticultural genome sequences, it has become relatively easier to utilize these resources to identify DNA sequences for both basic and applied research. Promoters play a key role in plant gene expression and the regulation of gene expression. In recent years, rapid progress has been made on the isolation and evaluation of plant-derived promoters and their use in horticultural crops, as more and more species become amenable to genetic transformation. Our understanding of the tools and techniques of horticultural plant biotechnology has now evolved from a discovery phase to an implementation phase. The availability of a large number of promoters derived from horticultural plants opens up the field for utilization of native sequences and improving crops using precision breeding. In this review, we look at the temporal and spatial control of gene expression in horticultural crops and the usage of a variety of promoters either isolated from horticultural crops or used in horticultural crop improvement.